AN OVERVIEW OF GEOGRAPHICAL, POLITICAL AND SOCIO ECONOMIC CONDITION OF POONCH, THE STATE OF JAMMU AND KASHMIR DURING DOGRA RAJ - Amar Jahangir; Dr. Syed Akmal Hussain Shah; Dr. Uzma Munshi (International Journal of Contemporary Issues in Social Sciences, 2024)
The region of Poonch holds immense historical significance as it has been ruled by outsiders and locals from time to time since 326 BC. In the light of the Amritsar Treaty of 16 March 1846, Dogra Gulab Singh purchased the territory of Kashmir along with its inhabitants and founded a new state called the State of Jammu and Kashmir. The Dogras ruled the state of Jammu and Kashmir for 101 years from 1846 to 1947 and the Poonch region was also under the influence of the Dogra rulers of Jammu and Kashmir in one way or another. The Dogra Raj usurped the political and social rights of the residents of Poonch region especially Muslims by imposing unnecessary and duail taxes. The people of Poonch strongly resisted the oppression of the Dogra rulers and started a movement against the Dogra Raj to get their political and social rights. The present research paper is an integrated account of the geographical, political, social and economic condition of Poonch Jammu and Kashmir during the Dogra Raj. This research is descriptive and historical in nature and is based on primary and secondary sources.